2001
DOI: 10.1063/1.1347018
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence method for detecting trace levels of iron in ultrapure silicon

Abstract: A nondestructive technique is presented for the determination of trace levels of interstitial iron contamination in ultrapure silicon. This approach is based on the well-known ability of iron to undergo a reversible pairing reaction with boron near room temperature. A variety of float-zoned silicon samples with low concentrations of boron (∼1011 cm−3) were subjected to thermal annealing treatments to study changes in the apparent boron concentration as determined by the standard method of comparing the photolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The A Si -Fe i defects were comprehensively investigated [31] and there are experiments, which indicate that a dissociation process indeed occurs [33,34]. In that case, the substitutional acceptor and the iron are fully separated.…”
Section: Discussionmentioning
confidence: 99%
“…The A Si -Fe i defects were comprehensively investigated [31] and there are experiments, which indicate that a dissociation process indeed occurs [33,34]. In that case, the substitutional acceptor and the iron are fully separated.…”
Section: Discussionmentioning
confidence: 99%
“…Defect formation during illumination could cause a reduction in B TO (BE) intensity. Here, the defect formation leads to a reduction of the luminescent excitonic transitions, according to Broussell et al [ 10 ]…”
Section: Resultsmentioning
confidence: 99%
“…Defect formation during illumination could cause a reduction in B TO (BE) intensity. Here, the defect formation leads to a reduction of the luminescent excitonic transitions, according to Broussell et al [10] Figure 5b is shown to check for the existence of an additional excitonic transition in the TA or NP region. This peak should be analogous to the P line of the In Si -Si i defect.…”
Section: Lid Related Ltpl Peakmentioning
confidence: 86%
See 2 more Smart Citations